What Impact Does Accreditation Have on Workplaces? A Qualitative Study to Explore the Perceptions of Healthcare Professionals About the Process of Accreditation - Alshamsi, Amna I.; Thomson, Louise; Santos, Angeli (Frontiers in Psychology, 2020)
Abstract Aim This study seeks to explore the emerging psychosocial risks of healthcare accreditation in workplaces and to understand healthcare professionals’ perceptions about work demands and the unexpected consequences such accreditation had placed upon them. Methods Twenty-seven semi-structured interviews and four focus group discussions were conducted with a variety of healthcare professionals, including doctors, nurses, pharmacists, and allied health professionals. The study was conducted in three public hospitals and a network of primary healthcare centers in the United Arab Emirates. Interviews and focus group discussions were transcribed and analyzed using a thematic analysis approach. Results The results have shown that a number of psychosocial risks were prevalent during the course of accreditation. Healthcare professionals faced increased work demands during such a process including increased working hours, increased working pace, perceived time pressure, and conflicted information. Such demands were perceived to influence their health and their families and patients’ care. In contrast, teamwork and co-worker support were vital to mitigate the effect of such demands. Implications This study has identified emerging risks during the process of accreditation. Findings show that the process of accreditation increases work-related risks before the inspection visit. These findings have significant implications in understating the way accreditation processes increase psychosocial risks; they also consolidate the idea that appropriate systems and support for HCPs should be a priority when planning for accreditation.